2023
DOI: 10.3390/cancers15133364
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Tolerance of N5 and N6 Chemotherapy Cycles in Combination with Dinutuximab Beta in Relapsed High-Risk Neuroblastoma Patients Who Failed at Least One Second-Line Therapy

Holger N. Lode,
Ruth Ladenstein,
Sascha Troschke-Meurer
et al.

Abstract: The anti-disialoganglioside (GD2) monoclonal antibody dinutuximab beta is approved for the maintenance treatment of high-risk neuroblastoma. Dinutuximab beta combined with different chemotherapy regimens is being investigated in various clinical settings. We conducted a retrospective clinical chart review of 25 patients with relapsed/refractory neuroblastoma who had failed ≥1 second-line therapy and received compassionate use treatment with dinutuximab beta long-term infusion combined with the induction chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
1
0
5
Order By: Relevance
“…В работе H. Lode и соавт. на группе больных с рецидивами НБ была показана возможность комбинации динутуксимаба бета с курсами полихимиотерапии по схемам N5/N6 (режим индукционной терапии группы GPOH) при отсутствии тяжелой и летальной токсичности с достижением лучшего ответа в 48% случаев [13]. При этом мАТ вводились длительной 24-часовой инфузией без добавления цитокинов c 5-го дня от начала химиотерапии (курсовая доза препарата 50 мг/м 2 ).…”
Section: обсуждение результатов исследованияunclassified
See 3 more Smart Citations
“…В работе H. Lode и соавт. на группе больных с рецидивами НБ была показана возможность комбинации динутуксимаба бета с курсами полихимиотерапии по схемам N5/N6 (режим индукционной терапии группы GPOH) при отсутствии тяжелой и летальной токсичности с достижением лучшего ответа в 48% случаев [13]. При этом мАТ вводились длительной 24-часовой инфузией без добавления цитокинов c 5-го дня от начала химиотерапии (курсовая доза препарата 50 мг/м 2 ).…”
Section: обсуждение результатов исследованияunclassified
“…Вопрос о дозовом режиме мАТ в рамках индукционной ХИТ также остается не решенным. В нашем пилотном исследовании мы использовали дозу, равную 50% от стандартной, применяемой в курсах постконсолидационной терапии (50 мг/м 2 /курс) [13]. Обоснованием выбора данного дозового режима являются результаты анализа, проведенного группой H. Lode и соавт.…”
Section: обсуждение результатов исследованияunclassified
See 2 more Smart Citations
“…Of HR-NBL patients, ~40% are refractory to, or relapse following, initial treatment [2][3][4]. For HR-NBL patients that are refractory to, or relapse during or after, their initial therapy, recent testing has shown that the addition of anti-GD2 mAb to chemotherapy (most often temozolomide with irinotecan, but other regimens have also been effective) enables objective responses in ~40% of patients, a result far superior to chemotherapy alone [5,6]. While this is clear progress, fewer than 20% of these patients seem to remain disease free long-term [5].…”
Section: Introductionmentioning
confidence: 99%